Variasi Kemampuan Siswa dalam Memahami Konsep Pembelajaran Matematika di Sekolah Dasar (SD) : Tantangan dan Solusi Pengajaran - Adzra Kamila Paustina; Dita Sabilla Azahra; Kowiyah Kowiyah (Jurnal Arjuna : Publikasi Ilmu Pendidikan, Bahasa dan Matematika, 2024)
This research discusses variations in students' ability to understand mathematical concepts as well as the challenges faced by teachers in adapting effective teaching strategies. Differences in mathematical understanding between students are often caused by factors such as educational background, learning motivation, and the teaching methods applied. This article examines adaptive teaching solutions, such as problem-based learning, the use of educational technology, and collaborative approaches to help teachers meet the needs of students with varying levels of understanding. The method used in this research is a descriptive qualitative method. By using observation and interviews as data collection methods, this research found that differences in students' mathematical understanding abilities were caused by internal and external factors, such as motivation, academic background, and teaching methods. The research results show that students have different abilities in understanding mathematics learning concepts.